PORTFOLIO SELECTION UNDER ARBITRAGE PRICING THEORY USING ECONOMETRIC APPROACH - Sukono, Sukono (JOURNAL OF QUANTITATIVE METHODS, 2010)
In this paper, we discuss the portfolio selection problem under the Arbitrage Pricing Theory (APT) using econometric approach. It is assumed that stock returns are analyzed following the APT. Factors in the APT are analyzed using an econometric approach, where the mean and non constant volatility are modeled using ARFIMA-GARCH models. The parameters of the long memory effects are estimated using the Range Scale (R/S) or Geweke and Porter-Hudak (GPH) method. Investment portfolio risk is measured by VaR (Value at- Risk) measure. Portfolio selection problem is formulated based on the risk measure of VaR, while the solution is carried out using the Lagrangian multipliers technique and the Kuhn-Tucker method. We provide an empirical study using some stocks that are traded in the capital markets of Indonesia